2021
DOI: 10.3389/fnbeh.2020.597902
|View full text |Cite
|
Sign up to set email alerts
|

Retaining Adolescent and Young Adult Participants in Research During a Pandemic: Best Practices From Two Large-Scale Developmental Neuroimaging Studies (NCANDA and ABCD)

Abstract: The novel coronavirus pandemic that emerged in late 2019 (COVID-19) has created challenges not previously experienced in human research. This paper discusses two large-scale NIH-funded multi-site longitudinal studies of adolescents and young adults – the National Consortium on Alcohol and Neurodevelopment in Adolescence (NCANDA) and the Adolescent Brain Cognitive Development (ABCD) Study – and valuable approaches to learn about adaptive processes for conducting developmentally sensitive research with neuroimag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Especially evident during the COVID-19 pandemic ( Nooner et al, 2021 ) is how life events can disrupt children and parents from participating in research. In turn, staying connected with participating youth and their parents during difficult times is especially important and timely to ensure that the study is not missing precisely the over-burdened families whose representation is crucial to ensure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially evident during the COVID-19 pandemic ( Nooner et al, 2021 ) is how life events can disrupt children and parents from participating in research. In turn, staying connected with participating youth and their parents during difficult times is especially important and timely to ensure that the study is not missing precisely the over-burdened families whose representation is crucial to ensure.…”
Section: Introductionmentioning
confidence: 99%
“…Further, with notable exceptions including by key members of our ABCD RW ( Cottler et al, 2016 , Cottler et al, 2017 , Montanaro et al, 2015 , Nooner et al, 2021 ), retaining sociodemographically diverse participants over time in longitudinal research studies has proven difficult for numerous previous studies and many scientific teams. As a consequence, racially, SES-, and demographically-diverse participants remain comparatively underrepresented across many existing large-scale longitudinal research studies.…”
Section: Introductionmentioning
confidence: 99%
“…Early inclusion of adolescents from marginalized groups in neuroscientific research (i.e., when writing the research proposal or setting up the research design) may aid in recognizing implicit biases that affect societal and scientific progress. Research projects should be more tailored to the needs, possibilities, and limitations of adolescents who participate in cohort studies (Jaddoe et al, 2006;Garavan et al, 2018;Hoffman et al, 2018;Nooner et al, 2021). We argue that having the right sampling and engagement strategies cannot be fulfilled without a sustainable researcher-community partnership, in which youth, youth workers, parents, teachers or communities are involved from the beginning of the research process (Weng et al, 2020;Saragosa-Harris et al, 2022).…”
Section: Citizen Sciencementioning
confidence: 99%
“…Science communication can positively aid in building trust within communities, which in turn can have positive effects on dismantling selection biases (Saragosa-Harris et al, 2022). Prior research has shown that building trust within communities encourages participation among marginalized groups (Jang and Vorderstrasse, 2019;Nooner et al, 2021). Science communication should be inclusive, and this requires expanding communication styles to other forms, such as such as writing blogs, making videos (with subtitles and preferable in multiple languages), and giving lectures and workshops at schools or community centers.…”
Section: Science Communication and Outreachmentioning
confidence: 99%
“…Researchers also presented potential solutions which could have been used for community members who may not have had access to a private location to participate in the study. Nooner et al recommended providing opportunities to participate in-person while adhering to social distancing guidelines, such as offering access to a designated, private research room with appropriate safety and cleaning protocols [57]. Additional suggestions to assist with virtual recruitment or engagement of participants for substance use studies involving virtual interviews or focus groups were detailed in Table 1.…”
Section: Reducing Apprehension Associated With Structural Barriers An...mentioning
confidence: 99%